DIAGNOSTIK KESULITAN BELAJAR MATEMATIKA MATERI STATISTIKA KELAS VIII SEKOLAH MENENGAH PERTAMA - Mirnawati, Mirnawati; Nurjannah, Nurjannah (Math Educa Journal, 2023)
This research is useful in diagnosing students’ learning difficulties for statistics material. This research was conducted at UPTD SMP Negeri 7 Sinjai. The researcher took two students of class VIII as subjects. Researchers used observation, interviews, documentation and diagnostic tests as data collection methods. Based on the research that has been done, the obstacles students face when working on statistical questions, there are still some who do not understand how to do the questions. And if there are new questions that are not similar to the examples given, students are wrong again in working on the problem. Efforts are being made in order to overcome student learning difficulties by practicing lots of questions and the teacher can understand how to capture and interest students so that it is easier to understand the material being explained.